Type II Opsins in the Eye, the Pineal Complex and the Skin of Xenopus laevis: Using Changes in Skin Pigmentation as a Readout of Visual and Circadian Activity - Bertolesi, Gabriel E.; Debnath, Nilakshi; Malik, Hannan R.; Man, Lawrence L. H.; McFarlane, Sarah (Frontiers in Neuroanatomy, 2022)
The eye, the pineal complex and the skin are important photosensitive organs. The African clawed frog, Xenopus laevis, senses light from the environment and adjusts skin color accordingly. For example, light reflected from the surface induces camouflage through background adaptation while light from above produces circadian variation in skin pigmentation. During embryogenesis, background adaptation, and circadian skin variation are segregated responses regulated by the secretion of α-melanocyte-stimulating hormone (α-MSH) and melatonin through the photosensitivity of the eye and pineal complex, respectively. Changes in the color of skin pigmentation have been used as a readout of biochemical and physiological processes since the initial purification of pineal melatonin from pigs, and more recently have been employed to better understand the neuroendocrine circuit that regulates background adaptation. The identification of 37 type II opsin genes in the genome of the allotetraploid X. laevis, combined with analysis of their expression in the eye, pineal complex and skin, is contributing to the elucidation of the role of opsins in the different photosensitive organs, but also brings new questions and challenges. In this review, we analyze new findings regarding the anatomical localization and functions of type II opsins in sensing light. The contribution of X. laevis in revealing the neuroendocrine circuits that regulate background adaptation and circadian light variation through changes in skin pigmentation is discussed. Finally, the presence of opsins in X. laevis skin melanophores is presented and compared with the secretory melanocytes of birds and mammals.